2014
DOI: 10.1002/mrm.25354
|View full text |Cite
|
Sign up to set email alerts
|

Using [1‐13C]lactic acid for hyperpolarized 13C MR cardiac studies

Abstract: This study demonstrated that the use of neat [1-(13) C]lactic acid as the DNP sample is a potential alternative to [1-(13) C]pyruvic acid for cardiac hyperpolarized (13) C MR studies. Hyperpolarized [1-(13) C]lactate may enable noninvasive assessment of cardiac PDH flux in cardiac patients in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
(74 reference statements)
2
25
0
Order By: Relevance
“…Rapid demagnetization of the label by means of molecule-specific T 1 relaxation (e.g., with a decay constant of 45 s for aqueous [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at 3T) mostly precludes reliable detection of additional intermediates or products. Due to this rapid demagnetization, HP 13 C studies with metabolically active probes are generally limited to very rapid biochemical pathways.…”
Section: Background On Methods For Probing Pathways Of Glucose Recyclmentioning
confidence: 99%
“…Rapid demagnetization of the label by means of molecule-specific T 1 relaxation (e.g., with a decay constant of 45 s for aqueous [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate at 3T) mostly precludes reliable detection of additional intermediates or products. Due to this rapid demagnetization, HP 13 C studies with metabolically active probes are generally limited to very rapid biochemical pathways.…”
Section: Background On Methods For Probing Pathways Of Glucose Recyclmentioning
confidence: 99%
“…Combined approaches using both [1- 13 C] and [2- 13 C] pyruvate [190, 191] or dual-enriched [1,2- 13 C 2 ] pyruvate allow for simultaneous investigation of pyruvate dehydrogenase flux, TCA cycle flux, and pH [192]. Other 13 C-labeled substrates applied to cardiac functional or metabolic imaging include [U- 13 C] α-ketobutyrate [193], [1- 13 C] lactic acid [194, 195], [1- 13 C] acetate [196199], 13 C urea [200], and [1- 13 C] butyrate [201, 202]. Recently, co-polarization of 13 C urea and [1- 13 C] pyruvate was demonstrated to simultaneously assess myocardial perfusion and metabolism [80].…”
Section: Applications Of Hyperpolarized 13c Mri To Pre-clinical Anmentioning
confidence: 99%
“…As the physiological plasma concentrations of lactate can be higher than those of pyruvate [1–10 m m versus 3–6 m m , respectively], the use of lactate may represent a viable and potentially safer alternative to pyruvate, as higher concentrations of lactate can be used to achieve an increase in SNR. Recently, it was shown that neat [1‐ 13 C]lactic acid without the addition of any solvent or glassing agent can be used for the preparation of hyperpolarized [1‐ 13 C]lactate in solution .…”
Section: Spectroscopy Of Cardiac Metabolismmentioning
confidence: 99%